Clays and Clay Minerals, Vol. 59, No. 1, 58–74, 2011. - Petrick, Kerstin; Diedel, Ralf; Peuker, Miriam; Dieterle, Matthias; Kuch, Paul; Kaden, Rene; Krolla-Sidenstein, Peter; Schuhmann, Rainer; Emmerich, Katja (My University, 2011)
The industrial assessment of ceramic clays commonly consists of the determination of just two parameters, the particle-size distribution and the chemical composition; other parameters may also be important, however. The aim of the present study was to show that a careful determination of the mineralogical phase content provides valuable additional information on the processing behavior of ceramic clays. Two ceramic clays (W1 andW2) from theWesterwald area, Germany, were evaluated as being the same with respect to industrial screening criteria, but showed different processing properties. In order to elucidate the different behaviors, both clays were investigated comprehensively using a multi-method approach combining physical-chemical and mineralogical methods. Different aggregation characteristics for the two clays were revealed by determining the grain-size distribution with and without Na-pyrophosphate as a dispersant. In addition, W1 showed a greater electrical conductivity and soluble-salt concentration which promoted dispersion behavior. The phase content was identified both for bulk materials and for several grain-size fractions by X-ray diffraction (XRD) and Rietveld analysis. The quantitative phase content was crosschecked with the chemical composition by X-ray fluorescence (XRF) analysis. Additional information was gathered by thermal analysis, cation exchange capacity (CEC) measurements, Mo¨ ssbauer spectroscopy, and optical microscopy. While bulk samples of W1 and W2 showed nearly the same mineralogical and chemical compositions, investigation of the clay-size fractions (0.6-2 mm , <0.6 mm) revealed differences in the composition of the 2:1 layer silicates. The percentages of smectite in the mixed-layer I-S, as well as the amount of kaolinite, discrete illite, and smectite were determined by one-dimensional XRD profile fitting (ODPF). Best-fitting results for W1 were achieved for a physical mixture of an illite-rich I-S mixed-layer mineral (R3 I(0.9)-S) with discrete smectite, whereas W2 was characterized by a greater proportion of smectite in the mixed-layer (R1 I(0.8)-S), without discrete smectite. Based on the different structural features of the swellable clays, a qualitative delamination model for the 2:1 layer silicates during processing of the clays was derived. The model provides a further approach, aside from aggregation characteristics, to help understand the clay-processing behavior, which was found to be different for the two ceramic clays investigated.
Character And Amount Of I-s Mixed-layer Minerals And Physicalchemical Parameters Of Two Ceramic Clays From Westerwald, Germany: Implications For Processing Properties
gsccm59108-pet.pdf-- 421KB
Keywords: Periodicals; Geology; Ceramic Clays; Delamination; Germany; Illite-smectite; Interstratification; Mixed-layer Minerals; Multi-method Approach; Processing Properties; Westerwald; XRD Profile Fitting